Cervicogenic Headache Alleviating by Spinal Adjustment in Combination with Extension-Compression Traction - Chu, Eric Chun Pu; Chu, Valerie Kok Yan; Lin, Andy Fu Chieh (Archives of Clinical and Medical Case Reports, 2019)
Cervicogenic headache (CGH) is a type of secondary headache where the symptoms originate from a dysfunction in the cervical spine. Mechanical cervical spine pathologies and dysfunction in the neck muscles may lead to CGH. This report presents a case of a female with fluctuating headache related to cervical disorders. Her headache was concurrently eliminated with resolution of the cervical disorder following spinal adjustment in combination with extension-compression traction. The efficacious response was attained over a year after completion of treatment. Strategies to release the strain of the supporting cervical extensors can be beneficial for alleviating CGH.